2011
DOI: 10.1007/s11738-011-0765-1
|View full text |Cite
|
Sign up to set email alerts
|

Profiling the differentially expressed genes in two rice varieties during rapid grain-filling stages

Abstract: Grain filling is an important agronomic trait, which directly affects the final yield of rice. Partially filled and empty rice grains are among the factors that limit the yield of MR219, one of the highest yielding rice varieties in Malaysia. In this study, the NSF 20 K rice oligonucleotide array, which contains 20,000 70-mer oligonucleotide probes, was used for direct comparison of the transcriptomes of MR219 and MR84 (a rice variety that has higher percentage of filled grains compared to MR219), during rapid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…A DNA microarray and real-time PCR analysis showed a group of genes relating to the starch metabolism, and with their enhanced expression profiles, the higher transcript levels in SS than IS at the early (EGS) and mid-grain-filling stages (MGS) [17] . The expression profiles of the miRNAs showed that 189 of them were differentially expressed between SS and IS [18] . However, the genome DNA sequence can only show, to a certain degree, the possible existence of corresponding functions of genes.…”
Section: Introductionmentioning
confidence: 99%
“…A DNA microarray and real-time PCR analysis showed a group of genes relating to the starch metabolism, and with their enhanced expression profiles, the higher transcript levels in SS than IS at the early (EGS) and mid-grain-filling stages (MGS) [17] . The expression profiles of the miRNAs showed that 189 of them were differentially expressed between SS and IS [18] . However, the genome DNA sequence can only show, to a certain degree, the possible existence of corresponding functions of genes.…”
Section: Introductionmentioning
confidence: 99%
“…The key stage of rice yield and quality formation is the grain-filling stage. 17,18 In the process of grain filling, the genetic characteristics of varieties are coordinated with the cultivation environment, and carbohydrate transport is sufficient, which dilutes the protein content of grains to a certain extent. In terms of the distribution of rice germplasm, the difference in latitude will affect the grain length.…”
Section: Discussionmentioning
confidence: 99%